Factors Affecting Price and Product Quality on Purchasing Decisions (Case Study at Indomaret Outlet Jln. Industri Branch of Medan) - Firman Wahyudi Sinaga (Institute of Computer Science (IOCS), 2021)
This study aims to determine the factors that influence the price and quality of products on purchasing decisions (Case Study at Indomaret Gerai, Jalan Industri Cabang Medan). The results of the study in an Adjust R Square value of 0.500 indicated that the contribution of the influence of price and product quality variables on consumer decisions to shop was 50%, while the remaining 50% was influenced by other variables not included in this research model. The results of research hypothesis testing using partial test (t test) found that the price variable has a significance of (0.000 <0.05) so there is a positive and significant influence on consumer decisions to shop at Indomaret Gerai Jln. Medan Branch Industry. The product quality variable has a significance of (0.000 <0. 05) so there is a positive and significant effect on product quality on consumer decisions to shop at Indomaret outlets Jln. Medan Branch Industry. Simultaneous test results (Test F) found that the significance value of 0.000 <0.05, so there is a positive and significant effect of price and product quality simultaneously on purchasing decisions at Gerai Indomaret Jln. Medan Branch Industry